2017
DOI: 10.1038/s41598-017-04347-8
|View full text |Cite
|
Sign up to set email alerts
|

Voxel-based morphometric brain comparison between healthy subjects and major depressive disorder patients in Japanese with the s/s genotype of 5-HTTLPR

Abstract: Individuals with s/s genotype of serotonin transporter gene-linked promotor region (5-HTTLPR), which appear with a high frequency in Japanese, exhibit more diagnosable depression in relation to stressful life events than those with the s/l or l/l genotype. We prospectively investigated the brain volume changes in first-episode and medication naïve major depression disorder patients (MDD) with the s/s genotype in Japanese. We assessed the differences between 27 MDD with the s/s genotype and 44 healthy subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…More recently, Igata et al . reported that the serotonin transporter genotype was associated with the volume of the gray matter in MDD patients 37 . Thus, further studies are required to explain the physiological systems in which IL-6 might be related to gray matter changes.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Igata et al . reported that the serotonin transporter genotype was associated with the volume of the gray matter in MDD patients 37 . Thus, further studies are required to explain the physiological systems in which IL-6 might be related to gray matter changes.…”
Section: Discussionmentioning
confidence: 99%
“…An fMRI study detected increased insular activation to facial expressions of disgust in MDD ( 46 ), reflecting an emotion processing bias. Local connectivity reduction ( 47 ) and GMV reduction ( 48 ) in the insula was positively correlated with the magnitude of anxiety in MDD. Besides, depressed patients with increased appetite had a lower anterior insular surface area, substantiating insula's role in interoceptive awareness as well as reward processing and emotion regulation ( 49 ).…”
Section: Discussionmentioning
confidence: 97%
“…At the same time, during the analysis of separate polymorphisms, this link was earlier detected. For example, such association was detected for 5-HTTLPR variable number tandem repeat (VNTR) polymorphism in the promoter region of the serotonin transporter gene SLC6A4 [ 86 ]. Besides, for one of alleles of this polymorphism, was found an association between stress and anxiety symptoms, which is moderated by 5-HTTLPR [ 87 ].…”
Section: Molecular Types Of Stressmentioning
confidence: 99%
“…A group of researchers Igata, N. et al, Caspi, A. et al, Zammit, S. et al, Karg, K. et al found that a short ‘S’ allele of the 5-hydroxytryptamine-linked polymorphic region polymorphism (5-HTTLPR) is associated with increased depression in a high-stress context [ 86 , 87 , 106 , 107 , 108 , 109 ]. Insertion deletion polymorphism (5-HTTLPR) is located in the promoter part of the serotonin transporter gene ( SLC6A4 ).…”
Section: Molecular Types Of Stressmentioning
confidence: 99%
See 1 more Smart Citation